2006
DOI: 10.7213/reb.v28i65.22162
|View full text |Cite
|
Sign up to set email alerts
|

TÁTICAS REPRODUTIVAS DE Mimagoniates microlepis (STEINDACHNER, 1876) (CHARACIDAE, GLANDULOCAUDINAE) NO RIO COLÔNIA PEREIRA, PARANAGUÁ, PARANÁ

Abstract: O estudo foi realizado no rio Colônia Pereira, pertencente à região hidrográfica Atlântico Sul. Foram feitas 13 coletas mensais entre março de 1995 e março de 1996, utilizando-se pesca elétrica. Foi determinada a variação da proporção sexual mensalmente e por classes de tamanho. Foi estimado o comprimento médio da primeira maturação (L50) e o comprimento médio em que 100% dos indivíduos são adultos (L100). A época reprodutiva foi determinada baseada na freqüência de indivíduos em reprodução e pela variação tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
0
7
0
10
Order By: Relevance
“…The influence of seasonal variations on the weight of individuals is considered a result of changes in resource availability, interacting with reproductive activity (Braga et al 2006). In the present study, the seasonal variation noted in the mean adjusted weight of individuals was equivalent in males and females, suggesting that feeding dynamics were more important than reproduction, even though females had higher mean adjusted weight than males.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The influence of seasonal variations on the weight of individuals is considered a result of changes in resource availability, interacting with reproductive activity (Braga et al 2006). In the present study, the seasonal variation noted in the mean adjusted weight of individuals was equivalent in males and females, suggesting that feeding dynamics were more important than reproduction, even though females had higher mean adjusted weight than males.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, the sexes may show differences in spatial distribution, with females occurring in areas that were not sampled out of the breeding season; then during the breeding season, both sexes are concentrated in the areas that were sampled, resulting in the higher proportion of females found. Braga et al (2006) suggested that mortality rate and growth can act differently on the sexes, also creating differences in the sex ratio. In this study the angular growth coefficient (b) of both sexes of B. stramineus was estimated at higher than 3 and males presented faster grew than females.…”
Section: Discussionmentioning
confidence: 99%
“…Quando a proporção sexual é analisada mensalmente são encontradas diferenças significativas nos meses de maio e junho com predomínio de machos e novembro com predomínio de fêmeas. Nos meses de maio e junho encontram-se as maiores freqüências de machos em maturação, sendo o período que precede à época reprodutiva (BRAGA, 2003). É possível que os machos estejam mais conspícuos nestes meses devido a confrontos que podem definir o acesso às fêmeas.…”
Section: Discussionunclassified
“…Sendo assim, os machos estariam mais sujeitos à captura, predominando nas amostras. No mês de novembro, final da época reprodutiva, foi encontrada alta freqüência de fêmeas recuperadas (BRAGA, 2003). Considerando que o período reprodutivo na gametogênese é caracterizado por uma grande alocação de energia, provavelmente este período pós reprodutivo pode ser caracterizado por grande esforço para obtenção de alimento e recuperação de energia.…”
Section: Discussionunclassified
See 1 more Smart Citation